2020
DOI: 10.2118/196015-pa
|View full text |Cite
|
Sign up to set email alerts
|

Annelida, a Robot for Removing Hydrate and Paraffin Plugs in Offshore Flexible Lines: Development and Experimental Trials

Abstract: Summary Methane hydrates and paraffin plugs on flexible lines are concerns in offshore production. They may stop wells for months, causing high financial losses. Sometimes, operators use depressurization techniques for hydrate removal. Another strategy is using coiled tubing or a similar unit to perform local heating or solvent injection. However, frequently these strategies are not successful. In those cases, a rig may perform the operation, or the line may be lost. We developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Although these methods are reasonably priced, one of the principal disadvantages is the plugging of perforations within wells, given the fact that scraped paraffin circulates through the well annulus. Furthermore, the wireline scrapers can get stuck in wells during post-cleaning operations [27,28]. The authors also suggested that the efficiency in gas-lift wells might be enhanced by using free pistons to remove organic wax deposits from the tubing string.…”
Section: Introductionmentioning
confidence: 99%
“…Although these methods are reasonably priced, one of the principal disadvantages is the plugging of perforations within wells, given the fact that scraped paraffin circulates through the well annulus. Furthermore, the wireline scrapers can get stuck in wells during post-cleaning operations [27,28]. The authors also suggested that the efficiency in gas-lift wells might be enhanced by using free pistons to remove organic wax deposits from the tubing string.…”
Section: Introductionmentioning
confidence: 99%
“…The most significant advantage of using chemical solvents is their pricing and the fact that they do not always require complicated instrumentation. However, this method is useful only for a specific type of wax deposit with a range of molecular weight, contingent upon pressure and temperature [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%